Is it safe to prescribe ascorbic acid for urinary acidification in stone-forming patients with alkaline urine? - Noureldin, Yasser A. (Turk J Urol, 2017)
OBJECTIVE: To study the effect of ascorbic acid (AA) supplementation on urinary pH, metabolic stone workup parameters, and development of de novo urolithiasis in stone-forming patients. MATERIAL AND METHODS: A retrospective review of the patients followed-up at a tertiary stone centre between September 2009 and October 2015 was performed. Patients with recurrent urolithiasis who received AA supplementation as a urinary acidifying agent were included in the study. Detailed metabolic stone work-up, including two 24-hour urine collections obtained pre- and post-AA supplementation were compared. In addition, imaging studies were reviewed to assess the development of de novo urolithiasis. RESULTS: Twenty-four patients were included in the study with a mean age of 60.6 years and a median daily AA dose of 1000 mg (range: 500–2000 mg). Median follow-up period was 22.6 months (range: 19.7–32.1). After AA supplementation, there was a significant decrease in urinary pH (7.6 vs. 6.9, p=0.02). Although there was no significant increase in the daily oxalate excretion, two patients (8.3%) had their AA dose reduced or discontinued due to de novo hyperoxaluria (342.9 vs 510.2 umol/day; p=0.75). Other serum and urinary parameters did not show any significant changes. Eight (33.3%) patients developed de novo urolithiasis with struvite and carbonate apatite being the major components. CONCLUSION: AA supplementation resulted in significantly lower urinary pH in patients with recurrent urolithiasis and alkaline urine pH. Prospective studies are needed to assess whether this reduction in urinary pH is associated with lower stone recurrence rates.